[BP.02.06] MATRIX METALLOPROTEINASE 2 AND 9 POLYMORPHISMS ARE ASSOCIATED WITH TARGET ORGAN DAMAGE IN OBESE RESISTANT HYPERTENSIVE SUBJECTS. (September 2017) - Ritter, A.; De Faria, A.; Sabbatini, A.; Barbaro, N.; Correa, N.; Brunelli, V.; Almeida, A.; Pires, N.; Modolo, R.; Moreno, H.
Abstract : Objective: The aim of this study is to analyze the influence of MMP-2 and -9 SNPs in obese hypertensive (HTN) and resistant hypertensive (RH) subjects, as well as their association with MMP-2 and 9 levels and target organ damage (TOD). Design and method: Two thousand and fifty six hypertensive subjects were divided in obese [body mass index (BMI higher than 30 kg/m 2 ) and non-obese (BMI lower than 30 kg/m 2 ). Genotypes were obtained by allelic discrimination assay using real time polymerase chain reaction. We compare clinical and laboratorial characteristics according to genotypes/haplotypes for MMP-2 (rs243865, rs243866 and rs2285053) and for MMP-9 SNPs (rs17577, rs17576 and rs391824) in obese HTN and RH subjects. Results: No difference in allele, genotype and haplotype frequencies for all polymorphisms between obese and non-obese HTN and RH were found. MMP-2, MMP-9 and their TIMPs levels were similar in obese HTN and RH according to MMP-2 and MMP-9 genotypes for all SNPs assessed. The same happened for clinical and biochemical characteristics among the genotypes in obese HTN and RH subjects except for some parameters: diastolic ambulatory blood pressure (BP) monitoring was higher in AG+AA compared to GG genotype for both rs243866 and rs243865 MMP-2 SNPs and the office diastolic BP was higher in AA than AG+GG genotype for rs17576 MMP-9 polymorphism in obese RH. However, when we compared the TOD according to genotype in obese RH we found that PWV was higher in CC genotype than CT for rs2285053 MMP-2 polymorphism [8.8 (8 – 11) vs 7.8 (6 – 8), p = 0.04]. Also, the AG+AA genotype for rs243866 and rs243865 MMP-2 polymorphisms have the same levels of LVMI and they are higher than GG genotype [116 ± 37 vs 138 ± 40, p = 0.04]. Finally, the microalbuminuria level was higher in AG+GG compared to AA genotype for rs17576 MMP-9 polymorphism. A multiple linear regression showed that only rs243866 and rs243865 are an independent predictor for LVMI levels after adjusted by gender, age, office BP, aldosterone and glucose levels. Conclusions: Therefore, the MMP-2 and -9 polymorphisms are associated with TOD in obese RH subjects.